Appendiceal Conduit: A Novel Technique to be Applied After Radical Cystectomy: A Case Report - Moudi, Emadoddin; Ghasemi Shektaie, Seyyed Hosein; Rostami, Ghasem (Urology Journal, 2020)
This paper introduces a novel technique, known as appendiceal conduit. It could be used as an alternative for ileal conduit and cutaneous ureterostomy, ultimately applied after radical cystectomy. The six-month follow-up indicated that the patient had appendix-stoma as nipple without any stenosis, nor did he have any hydronephrosis, as confirmed by abdominal sonography.